Direct Fitting of Analytical Potential Functions to Diatomic Molecular Spectroscopic Data - Seto, Jenning (University of Waterloo, 2000)
The standard practice of spectroscopic data reduction is generally to fit data to level energy expansions in terms of the vibrational and rotational quantum numbers. However, the utility of such expressions is limited because they extrapolate poorly and they need very large sets of parameters, many of which have no independent physical significance. One method of addressing these problems is to fit the spectroscopic data directly to analytical potential energy functions incorporating the natural physical behaviour of the molecule in question. Although there have been a number of successful applications of this approach, there are still certain problems associated with the types of potential forms being used. This thesis will explore some of these problems and determine how effective the potential forms being used are for a number of specific cases.
Keywords: Chemistry; Direct Potential Fitting; Spectroscopy; Computer Program; Diatomics